Acquired Aorto-Right Ventricular Fistula following Transcatheter Aortic Valve Replacement - Muhammad Tariq Shakoor; Ashequl M. Islam; Samia Ayub (Case Reports in Cardiology)
Transcatheter aortic valve replacement (TAVR) techniques are rapidly evolving, and results of published trials suggest that TAVR is emerging as the standard of care in certain patient subsets and a viable alternative to surgery in others. As TAVR is a relatively new procedure and continues to gain its acceptance, rare procedural complications will continue to appear. Our case is about an 89-year-old male with extensive past medical history who presented with progressive exertional dyspnea and angina secondary to severe aortic stenosis. Patient got TAVR and his postoperative course was complicated by complete heart block, aorto-RV fistula, and ventricular septal defect (VSD) formation as a complication of TAVR. To the best of our knowledge, this is the third reported case of aorto-RV fistula following TAVR as a procedural complication but the first one to show three complications all together in one patient.